The influence of hallux valgus on pelvis and lower extremity movement during gait [Vliv valgózní deformity palce na pohyb pánve a dolních končetin při chůzi] - Miloslav Klugar; Milan Elfmark; Zdenek Svoboda; Miroslav Janura; Jitka Kozaková (Palacky University, 2011)
BACKGROUND: The hallux and the first metatarsophalangeal joint play a major role in load transmission during walking. OBJECTIVE: The main aim of this study was to investigate differences in kinematics of the pelvis and lower extremities during gait by comparing people with hallux valgus (HV) and a control group (CG). METHODS: We compared subjects with asymptomatic bilateral HV (n = 6, 57.8 ± 5.64 years) with those who had CG (n = 11, 50.7 ± 4.41 years). Gait analysis was investigated using an optoelectronic system Vicon MX. The subjects walked at self-selected speeds. In total, five trials of each subject were analyzed. The statistical processing was performed by means of the Student t-test. The effect size was determined using the ω2 measure. RESULTS: In people with HV there was a significantly smaller maximum of dorsal flexion during the stance phase (p < 0.01, ω2 > 0.06) and a greater maximum of plantar flexion at the beginning of the stance phase (p < 0.01, ω2 > 0.06). The maximum of knee extension at the end of the swing phase was significantly greater (p < 0.01, ω2 > 0.06) in subjects with HV. In the frontal plane, a significantly smaller maximum of hip abduction (p < 0.01, ω2 > 0.06) during the gait cycle was observed in people with HV. The range of the pelvic obliquity (p < 0.01, ω2 > 0.06) and the pelvic rotation (p < 0.01, ω2 > 0.06) were significantly smaller in people with HV. CONCLUSION: This study demonstrated that HV does not exclusively concern the foot. The valgus deformity of the big toe can negatively influence function of the lower extremities and can cause overloading of those segments as well. [VÝCHODISKA: Palec a I. metatarzofalangeální kloub hrají klíčovou úlohu v přenosu zatížení při chůzi. CÍLE: Účelem této studie bylo analyzovat a interpretovat rozdíly v kinematických parametrech chůze u osob s hallux valgus v porovnání s kontrolní skupinou. METODIKA: Porovnávali jsme osoby s asymptomatickou oboustrannou valgózní deformitou palce (n = 6; 57,8 ± 5,64 let) s kontrolní skupinou (n = 11; 50,7 ± 4,41 let). Provedení chůze jsme analyzovali pomocí optoelektronického systému Vicon MX. Každý proband byl instruován k chůzi svým přirozeným způsobem i tempem. Vyhodnotili jsme 5 pokusů u každého probanda. Získaná data jsme statisticky zpracovali pomocí párového studentova t-testu. Věcnou významnost jsme vypočítali pomocí koeficientu "effect size" (ω2). VÝSLEDKY: U osob s HV jsme nalezli statisticky i věcně významně menší maximum dorzální flexe v průběhu stojné fáze (p < 0,01; ω2 > 0,06) a větší maximum plantární flexe na počátku stojné fáze (p < 0,01; ω2 > 0,06). Maximum extenze v kolenním kloubu bylo osob s HV v závěru švihové fáze u statisticky i věcně významně větší (p < 0,01; ω2 > 0,06). Ve frontální rovině jsme pozorovali statisticky i věcně významně menší maximum abdukce v kyčelním kloubu u osob s HV (p < 0,01; ω2 > 0,06). Rozsah pohybu pánve ve frontální a transverzální rovině byl statisticky i věcně významně menší u osob s HV (p < 0,05; ω2 > 0,06). ZÁVĚRY: Výsledky této studie ukazují, že HV nepředstavuje problém pouze v oblasti nohy. Valgózní deformita palce může negativně ovlivnit funkci všech segmentů dolní končetiny a vést k jejich přetížení.]